1990
DOI: 10.1016/0014-5793(90)81519-t
|View full text |Cite
|
Sign up to set email alerts
|

Serine phosphorylation of biosynthetic pro‐urokinase from human tumor cells

Abstract: Phosphorylation is a potent mechanism regulating the activity of many intracellular enzymes. We have discovered that the product of the human urokinase plasminogen activator gene, pro-uPA, is phosphorylated in serine in at least two human cell lines. Phosphorylation occurs within the cell during biosynthesis, and phosphorylated intracellular pro-uPA is secreted into the medium. Of the secreted pro-uPA molecules, 20-50% are phosphorylated in serine, thus representing a meaningful fraction of the total biosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…The results obtained are in line with those obtained by Mastronicola et al [12] in the case of P-Ser of u-PA where two phosphorylation sites have been demonstrated.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results obtained are in line with those obtained by Mastronicola et al [12] in the case of P-Ser of u-PA where two phosphorylation sites have been demonstrated.…”
Section: Discussionsupporting
confidence: 92%
“…From the quantitative analysis on the level of phosphorylation obtained by HPLC, it can be concluded that only a limited number (1 or 2) of the Ser and Thr residues, present in the molecules analyzed, should be susceptible to phosphorylation in agreement with previous data on Ser-phosphorylation of u-PA molecules secreted by tumor cells [12].…”
Section: Immunological Recognition Of P-ser and P-thr Residues In T-psupporting
confidence: 87%
See 1 more Smart Citation
“…Urokinase function is also subjected to post-translational control; we found that the human proenzyme undergoes intra-cellular serine phosphorylation in A431 human carcinoma cells, resulting in a reduction of its sensitivity to the inhibitor PAI-1 (22)(23)(24). According to other reports, phosphorylated urinary urokinase activates plasminogen with a greater catalytic efficiency and is neither inhibited by PAI-1 nor by PAI-2 (25).…”
Section: /mentioning
confidence: 99%
“…It is possible that the conformation attained by the mature protein, either recombinant or secreted from A431 cells may not totally resemble that of intracellular pro-uPA (22). Alternatively, an unknown kinase may be responsible for the modification of Ser 303 in vivo, provided its activity is regulated by PKC.…”
mentioning
confidence: 99%